Preliminary Study on the Visualization and Quantification of Elemental Compositions in Individual Microdroplets using Solidification and Synchrotron Radiation Techniques - Chang-Jin Ma; Susumu Tohno; Mikio Kasahara (Asian Journal of Atmospheric Environment, 2011)
Quantifying the solute composition of a cloud droplet (or a whole droplet) is an important task for understanding formation processes and heating/cooling rates. In this study, a combination of droplet fixation and SR-XRF microprobe analysis was used to visualize and quantify elements in a micro-scale droplet. In this study, we report the preliminary outcome of this experiment. A spherical micro-scale droplet was successfully solidified through exposure to α-cyanoacrylate vapor without affecting its size or shape. An X-ray microprobe system equipped at the beam line 37XU of Super Photon ring 8 GeV (SPring-8) was applied to visualize and quantify the elemental composition in an individual micro-scale droplet. It was possible to reconstruct 2D elemental maps for the K and Cl contained in a microdroplet that was dispensed from the 10-ppm KCl standard solution. Multi-elemental peaks corresponding to X-ray energy were also successfully resolved. Further experiments to determine quantitative measures of elemental mass in individual droplets and high-resolution X-ray microtomography (i.e., 3D elemental distribution) are planned for the future.